Penerapan Metode Multi Factor Evaluation Process Dalam Penilaian Kinerja Karyawan Bagian Produksi CNC - Muhamad Bayu Aditya Pratama; Tukino; Huda, Baenil; Hilabi, Shofa Shofiah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
Reflecting on the problems that have occurred previously due to the company's lack of managing its human resources properly, causing chaos in the production department. This problem arises because in the company there are too many PKWT (Specified Time Work Agreement) employees working, causing instability in the production line. When PKWT's work period was about to end, many prospective replacement employees resigned during the training stage because they could not stand the pressure of working in hot room temperatures in making wheel rims. This causes the company to have to look for other candidates which will take many time, while production must continue as usual. Of course, this will have a negative impact on the company if it continues in the future. Therefore, good human resource management is needed to ensure that the Company's goals are achieved efficiently and effectively. One of the things that must be done in managing human resources is monitoring and viewing employee performance. Because by knowing the performance of the Company's employees, you can ensure that tasks are carried out to predetermined standards and achieve optimal results. Employee performance assessments are carried out in the CNC section, especially on production results. This assessment aims to assess employee performance objectively and fairly, so that it can be used as an evaluation for decision making such as contract extensions, the appointment of permanent employees, promotions, and others. This performance assessment can certainly really help companies manage their human resources and reduce the impact of company losses in the future. Apart from that, this assessment is very important for a company to ensure the creation of a good quality product. The author uses a computerized system using Python and the Multi Factor Evaluation Process method to evaluate employee performance. The reason the author uses this method is because of its ability to make precise judgments based on predetermined criteria values. The data in this research is CNC production data recorded for one month. By assessing 46 employees based on data on Total Production, OK Goods (according to SOP), and Reject Goods (Not Good). The results of implementing MFEP in this performance assessment produced the highest score of 9.2 while the lowest score was 3.0.